BENEFITS OF STEEPING BLACK TEA AS A NEGATIVE CONTRAST MEDIUM ON CT UROGRAPHY EXAMINATION - Yudha, Sagita; Hadisaputro, Suharyo Hadisaputro; Ardiyanto, Jeffri; Mulyantoro, Donny Kristanto; Masrochah, Siti (Postgraduate Program , Poltekkes Kemenkes Semarang, 2020)
The use of water as a contrast medium requires large amounts of water to fill the lumen of the Urinary Tractus and more water is reabsorbed by the body than is secreted into urine. Steeping Black tea contains Caffeine which is able to increase blood flow in the kidneys thus inhibiting the process of absorption of Na, Ca and Mg causing stimulation of the kidneys to increase the amount of urine production. The purpose of this study is to prove that drinking black tea can increase urine production as a negative contrast medium to see differences in the distension and density of the Urinary Tract on CT Urography examination. This type of research uses True Experimental with Pretest-Posttest Control Group Design research design. Patients selected by Simple Random Sampling. Analysis: Paired t test and Independent t test. The results of the study of the use of 600 ml steeping Black Tea as a negative contrast medium on CT Urography examination did not show the difference in mean difference between the left renal Pelvis p value 0.956, Left UVJ 0.640, Right UVJ 0.935 while on the right renal Pelvis p value 0.001 showed differences in mean difference between the left renal Pelvis p value 0.956, Left UVJ 0.640, Right UVJ 0.935 while on the right renal Pelvis p value 0.001 intervention and control group. Hasil pengukuran p valueÂ densitas Vesika urinaria sebesar 0,678. Conclusion: Black tea can be used as a negative contrast medium on CT Urographic examination but when compared with mineral water it does not show a significant difference.